Testimonia Koleksiyonları ve Hıristiyan Apolojetik-Polemik Eserlerdeki Şahit-Metinlerin Kullanımı/Testimonia Collections and Using Proof-text in Christian Apological Literature - Zeynep Yücedoğru (Oksident, 2023)
The early Christians compiled lists of selected passages from the Jewish scriptures and preserved them as sacred writings. When the content of these extract collections is analysed, the anti-Jewish apologetic-polemic characteristic stands out. These extract collections were also used in catechist education. Over time, early Christians attributed the status of testimonia to certain passages that became prominent among other proof-texts, so that, compared to other circulating proof-texts, the testimonia passages were regarded as testimonials to the theological truth that did not even require interpretation. The creation and preservation of testimonia collections became not only a technical activity for Christians but also a tradition that shaped early Christian theology around certain central passages. Traces of this tradition can be seen in the works of the early church fathers and among later Christians. Greek, Latin and Syriac testimonia collections were translated into Arabic and used as sources of biblical proof-texts in both oral debates against Muslims and apologetic-polemical works. The primary purpose of this study is to examine the connection between the biblical quotations in the works of Christian Arab writers of different periods and the testimonia tradition. This study focuses on how biblical testimonia, which accompanied theological arguments from the first centuries onwards, were used and interpreted in Christian authors' apologetics and polemics against Muslims together with the strategy of "arguing from the book" and what are the similarities and differences in scriptural argumentation of Arab Christian authors compared to the previous testimonia tradition.